The limits of emancipation: land regulation and housing struggle - Ana Luiza Vieira Gonçalves (Geografares, 2022)
The present article seeks to discuss the limits of the emancipatory potential of the struggle for housing, from the identification of different actors in the forms of management and agency of territories and marginalized populations in the city of São Paulo, interlacing agents who dispute the protagonism of political action and control in the territories of occupations in the city's South Zone, with the analysis centered on the Anchieta occupation - the field of master's research to which the article relates -, located in Grajaú, South Zone, relating itself to other occupations in the region. The central axis is the analysis of how the strategies of financing, regulation and physical intervention of the State and the population in the built environment, as well as the forms of organization and institutionalization of public policies and forms of social organization are intertwined with the production and reproduction of urban and regional space, from the new modulations of neoliberalism in Brazil.
Keywords: neoliberalism; violence; urban occupations